Carboxyhemoglobin (COHb): Unavoidable Bystander or Protective Player? - André Carrola; Carlos C. Romão; Helena L. A. Vieira (MDPI AG, 2023)
Carbon monoxide (CO) is a cytoprotective endogenous gas that is ubiquitously produced by the stress response enzyme heme-oxygenase. Being a gas, CO rapidly diffuses through tissues and binds to hemoglobin (Hb) increasing carboxyhemoglobin (COHb) levels. COHb can be formed in erythrocytes or in plasma from cell-free Hb. Herein, it is discussed as to whether endogenous COHb is an innocuous and inevitable metabolic waste product or not, and it is hypothesized that COHb has a biological role. In the present review, literature data are presented to support this hypothesis based on two main premises: (i) there is no direct correlation between COHb levels and CO toxicity, and (ii) COHb seems to have a direct cytoprotective and antioxidant role in erythrocytes and in hemorrhagic models in vivo. Moreover, CO is also an antioxidant by generating COHb, which protects against the pro-oxidant damaging effects of cell-free Hb. Up to now, COHb has been considered as a sink for both exogenous and endogenous CO generated during CO intoxication or heme metabolism, respectively. Hallmarking COHb as an important molecule with a biological (and eventually beneficial) role is a turning point in CO biology research, namely in CO intoxication and CO cytoprotection.